Responding to Harm: The Challenge of Children’s Perspectives - Anthony Charles (Journal of Victimology and Victim Justice, 2019)
Drawing upon research undertaken in South Wales, this article explores children's views of what it means to be a 'victim' of crime. Moving beyond more orthodox understandings of crime, and reflecting upon real-life experiences associated with being a 'victim', children articulated an almost zemiological perspective of 'harm', passionately argued that they were not taken seriously by an adult-led criminal justice system and suggested that system did not address their needs. This article offers new and transformative understandings of child victimhood and poses significant challenges for those who develop and implement victim policy and service provision.